"Our academics are intellectually colonised": Multi-languaging and Fees Must Fall. Issue 1 (23rd March 2018) - Makalela, Leketi
Abstract: There is no doubt that the Fees Must Fall student movement in the South African higher education system has received wide-ranging documentation and world-wide coverage. A plethora of studies and documentaries on the students', lecturers' and parents' involvement have seized the moment to explain the complex dynamics of the most unprecedented student revolution in the new sociopolitical dispensation since the fall of apartheid in 1994. While social scientists agree that ways of managing 'revolutions' in the 21st century using the old apartheid style of riot control is both obsolete and irrelevant due to more fluid ways of mass mobilisation, very little is known about the intricacies of language use and how this presents novel ways of knowing and self-affirmation among postmodern students. In this paper, I analyse key instances of complex multilingual encounters in the process of meaning-making during the protests. I show how multilingualism and the exchange of ideas in more than one language has been instrumental in pulling the demonstrators together across the wider spectrum of languages spoken in south Africa – something that debunks myths around intelligibility levels in African languages. Given the efficacy of this complex web of communication in times of distress, despair, and dispossession, I take a linguistic position that multi-languaging is an effective mass-mobilisation strategy and a potential tool to decolonise formal university discourses that are largely monolingual and exclusionary. Implications for learning and teaching are highlighted at the end of the paper.